2005
DOI: 10.1002/cne.20853
|View full text |Cite
|
Sign up to set email alerts
|

Connections of the lateral and medial divisions of the goldfish telencephalic pallium

Abstract: Biotinylated dextran amine and fluorescent carbocyanine dye (DiI) were used to examine connections of the lateral (Dl) and medial (Dm) divisions of the goldfish pallium. Besides numerous intrinsic telencephalic connections to Dl and Dm, major ascending projections to these pallial divisions arise in the preglomerular complex of the posterior tuberculum, rather than in the dorsal thalamus. The rostral subnucleus of the lateral preglomerular nucleus receives auditory input via the medial pretoral nucleus, latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

68
532
5
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(608 citation statements)
references
References 69 publications
68
532
5
3
Order By: Relevance
“…Similar findings have been reported in several other studies (10,11,17,18). Thus, we believe that the results for the fish in the A-SAL and S-SAL groups were opposite in terms of memory consolidation of the inhibitory avoidance task due to the absence of cerebellar modulation in limbic structures in the ablation group, especially in the MP, which is thought to be homologous to the amygdala (29)(30)(31).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings have been reported in several other studies (10,11,17,18). Thus, we believe that the results for the fish in the A-SAL and S-SAL groups were opposite in terms of memory consolidation of the inhibitory avoidance task due to the absence of cerebellar modulation in limbic structures in the ablation group, especially in the MP, which is thought to be homologous to the amygdala (29)(30)(31).…”
Section: Discussionsupporting
confidence: 89%
“…The lateral pallium is associated with spatial and temporal memory, and appears to be homologous to the hippocampus of vertebrates, while the medial pallium (MP) is related to emotional memory and has been suggested to be homologous to the amygdala of mammals (28,29). Furthermore, recent studies have demonstrated the existence of connections between the cerebellum and the MP in goldfish and other teleost fish (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…This organization led early comparative anatomists to the view that the telencephalon in teleosts EDITORIAL was entirely subpallial. But as was the case for birds, studies on molecular and hodological features of the forebrain in these fishes have led to the realization that pallial-equivalent cell groups are present despite the location of these groups below the ventricle (Wullimann and Mueller, 2004;Yamamoto et al, 2007;Northcutt, 2006;Nieuwenhuys, 2009;Mueller et al, 2011HarveyGirard et al, 2012Ganz et al, 2012). Recent hodological, neurochemical, and molecular studies suggest that lampreys also possess pallial and subpallial homologues (Murakami et al, 2001;Stephenson-Jones et al, 2012;Sugahara et al, 2013).…”
mentioning
confidence: 99%
“…As is the case for birds, teleosts have two major pallial regions, lateral and medial, that receive sensory inputs from the diencephalon Ito, 2005, 2008;Northcutt, 2006). One hypothesis considers the lateral part to be homologous to the hippocampus while the medial part would represent the claustroamygdaloid complex (Northcutt, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation